DIFFICULTY IN BREATHING DUE TO ACCIDENTAL EXPOSURE TO HYPOCHLORITE SOLUTION IN ENDODONTIC TREATMENTREATHING DUE TO ACCIDENTAL EXPOSURE TO HYPOCHLORITE SOLUTION IN ENDODONTIC TREATMENT - Buddiwati Punta (Journal of Dentistry Indonesia, 2006)
An important phase of endodontic treatment is the irrigation of the root canal system. Desirable functions of irrigation are antimicrobial activity, dissolution of necrotic tissue, and non toxicity to the periradicular tissue. Toxicity of NaOCl solution on vital tissue is still controversial. Severe complications may occur if this solution is inadvertently exposed to the oral mucosa, and it is very hazardous. The purpose of this paper is to caution dentists on the hazards of using NaOCl irrigation in endodontic treatment. A case is presented in which 2.5% NaOCl solution was accidentally streaming into the patient's throat because the irrigating needle was not securely attached to the syringe, with the result that the patient had difficulty in breathing. The patient was promptly taken to a pulmonologist, internist, and ENT. The patient was given dexamethasone 10 mg iv injection, delladryl 1 cc iv, and nebulizer with 1 ampoule of steroid, 1 ampoule of ventolin and 5 cc NaCl 3x within 24 hours, and after 24 hours the condition was increased. From this case it is concluded that the 2.5% NaOCl solution is very alkaline and irritating, resulting in deem of the larynx and plugging up of the respiratory system. Clinicians need to be cautious in using NaOCl solution to avoid endangering the patient's life.